EVALUATION OF THE RESPIRATORY MUSCLE STRENGTH AND THE PEAK FLOW IN FIBROCYSTIC TEENAGERS AND CHILDREN (Fiep Bulletin - online, 2013)
Introduction: Cystic Fibrosis (CF) is characterized as a chronic obstructive pulmonary disease, increasing the number of electrolytes in sweat and exocrine pancreatic failure. It is possible that the respiratory muscle strength (RMS) is decreased in this population and that selected body postures entail in a higher reduction of the RMS and peak flow. Goal: To watch if there is reduction of maximum inspiratory pressure (MIP), maximum expiratory pressure (MEP) and peak flow in fibrocystic patients under different body postures. Materials and Methods: An observational, descriptive and cross sectional study, built of six patients from both genders (male and female) and aged between 6 and 18 years old. It was done three different measurements of the RMS using a digital vacuum manometer (MVD 300 Globalmed®) and peak flow (Peak Flow Meter®)  in the Fowler 450, sedestation (sitting in a 90o position) and orthostasis position, the vital signs were also evaluated during the postural assessment. Results: Comparing the MIP and MEP values against the predicted values there were not any variations (MIP = 67.00 and 69.18 cmH2O and MEP = 86.00 and 90.60 cmH2O) (p = 0.917). Orthostasis showed the highest MIP and MEP values (68.50 cmH2O and 95.50 cmH2O respectively). It is possible to highlight there was a variation of the MIP in Fowler 45o for orthostasis (p= 0.003), while MEP did not show any significant variation between the body postures. The peak flow, on the other hand, was statistically decreased in these patients (p = 0.046). Conclusions: The RMS of the fibrocystic patients analyzed did not change in relation to what was predicted, but the Fowler 45o for orthostatic showed a significant variation. Orthostasis resulted in the highest values of MIP and MEP. The peak flow showed an arway obstruction and did not vary changing the body postures.
Keywords: Cystic Fibrosis; different body postures; manovacuometry